The Assistance of English Learning during the Covid-19 Pandemic in Jakarta’s Orphanage - Danti Pudjiati; Vera Yulia Harmayanthi; Venti Mawarni; Tira Nur Fitria (LPPM ITB AAS Indonesia Surakarta, 2022)
The community partnership program was administered in the form of online assistance for English learning of the grade X of senior high school students. The partner was an orphanage belonging to the local government in DKI Jakarta Province. The objective of the assistance program was to motivate the English learning and find the solution for their problem in understanding English at school. Fourteen boys participated in this program. One meeting was held in the orphanage with the person in charge and four asynchronous meetings with the participants were conducted in three months. In practice, most of the students showed their motivation in terms of involving the English discussion and completing the tasks as well. Unfortunately, the signal of internet connection did not support the online learning and some of the students were in quarantine due to coronavirus infection. In conclusion, they were not ready to study online as several obstacles arose such as the weak internet signal and their absences. Therefore, they need to study English in a room with a teacher where all of them can communicate with each other in a friendly atmosphere. By doing so, they are possible to improve their English mastery.